Radiotherapy for subfoveal neovascularisation associated with pathological myopia: a pilot study. Issue 7 (1st July 2000) - Kobayashi, Hiroshi; Kobayashi, Kaori
Abstract : BACKGROUND/AIM: Limited treatments are available for this disease process. A pilot study was performed to determine the toxicity and efficacy of external beam radiotherapy for subfoveal neovascular membranes and subretinal haemorrhage associated with pathological myopia. METHODS: A randomised, prospective study was carried out on 39 patients with subfoveal neovascularisation associated with high myopia. 20 patients underwent radiotherapy and the remaining 19 were observed as a randomised comparison group. All patients were followed up for at least 24 months. Subfoveal choroidal neovascular membranes (CNVMs) were treated with a single lateral 6 MV photon beam to a dose of 10 Gy in five fractions over 5–7 days. Post-treatment measurements included corrected visual acuity, area of CNVM, and occurrence of radiotherapy related complications, and adverse reactions. To assess changes of area of CNVM, the initial (pretreatment) size of the CNVM was set to 100%, and all post-treatment measurements were normalised relative to the initial size. RESULTS: No significant acute morbidity was noted. There was no significant difference in age, sex, refractive error, visual acuity, and area of CNVM at baseline between the treatment group and control group. The mean change of the size of the CNVM for 2 years was 155% (SD 156%) in the treatment group and 249% (124%) in the control group. The increase in the size of CNVM in the treatment group was significantly smaller than that in the control group (p = 0.0452). In the treated eyes, the visual acuity before and 1 and 2 years after radiotherapy were 0.111 (22.2/200), 0.091 (18.2/200), and 0.086 (19.2/200), respectively. In the control eyes, visual acuity before and 1 and 2 years after the start of the follow up were 0.141 (34.2/200), 0.089 (17.8/200), and 0.063 (12.6/200). The patients in the treatment group showed no significant change for 2 years, and those in the control group showed a significant decrease in the visual acuity (p = 0.0033). The changes of logMAR of visual acuity for 2 years after the start of the follow up were +0.019 (0.443) in the treatment group and +0.347 (0.374) in the control group. There was a statistically significant difference between them (p = 0.0173). Multiple regression analysis on the treatment group showed that the most significant predictive variable for the visual acuity 2 years after the treatment was the combination of pretreatment visual acuity and refractive error. CONCLUSIONS: Radiotherapy appeared to have a favourable treatment effect in eyes with subfoveal neovascular membranes and haemorrhage associated with pathological myopia. Further investigation is needed to evaluate the efficacy of radiotherapy for subfoveal neovascularisation associated with pathological myopia.